Kebijakan Formulasi Pemanfaatan Pengaruh (Trading In Influence) Jabatan Publik Sebagai Tindak Pidana Korupsi - Gresye A Pesireron; Elsa Rina Maya Toule; Juanrico Alfaromona Sumarezs Titahelu (Faculty of Law, Universitas Pattimura, 2022)
Introduction: This article examines the judges' Trading in influence. Trading in influence is a type of corruption crime regulated in the provisions of article 18 (a) and article 18 (b) of the Anti-Corruption Convention (KAK) or referred to as UNCAC 2003.Purposes of the Research: This study aims to analyze and explain the process of Trading in influence. Methods of the Research: This research uses empirical juridical research with this type of research being descriptive analysis. The technique of collecting legal materials is by conducting library research on legal materials, namely primary, secondary, and tertiary legal materials.Results of the Research: Legal analysis techniques obtained and classified qualitatively.Based on the results of research and discussion, it can be concluded that the form of the use of influence is divided into two parts, namely active trading in influence and passive trading in influence. Knowing the number of cases that often occur using the modus operandi of Trading in influence and processed using the bribery article even though there are differences between the two plus because there is no legal regulation regarding this type of corruption, prevention efforts for the future have been carried out by seeking to relate this act into the TPK Bill article 4 and adopted in the RUU-KUHP regulated in article 691.